Penanaman Karakter Disiplin Siswa Kelas Xi Di MAS Aisyiyah Melalui Pendektan Islami - Tanjung, Nurfadilah (Journal of Sustainable Education, 2025)
Instilling discipline is an important aspect in shaping students' personalities, leading to a responsible and orderly attitude in their daily lives. This study aims to describe the process of instilling discipline in eleventh-grade students at MAS Aisyiyah through an Islamic approach that integrates religious values into learning activities and school life. The method used is descriptive qualitative with data collection techniques in the form of observation, in-depth interviews, and documentation. The results of the study indicate that the implementation of discipline is effective through teacher role models, habituation of religious activities, and consistent application of Islamic law-based rules. Supporting factors for success include active teacher involvement and student awareness, while the main challenges come from external environmental influences and technological developments that require synergy between schools, families, and communities to overcome them. This study confirms that the Islamic approach can be an effective medium in developing students' discipline in a religious-based school environment.